2017
DOI: 10.1515/hukin-2017-0112
|View full text |Cite
|
Sign up to set email alerts
|

Sports Activity Following Cementless Metaphyseal Hip Joint Arthroplasty

Abstract: An adequate level of physical activity has a substantial effect on both mental and physical human health. Physical activity is largely dependent on the function of the musculoskeletal and articular system. One of the most frequent diseases of this system is degenerative joint disease. Due to the changing and more demanding lifestyles and patients’ willingness to be involved in sports activity, the expectations of hip joint arthroplasty are becoming increasingly high. Alleviating pain ceases to be the only reas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…To maintain adequate bone density, specific load to the bone tissue is needed. This is achieved by the participation in recreational-level amateur sports and through moderate physical activity [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…To maintain adequate bone density, specific load to the bone tissue is needed. This is achieved by the participation in recreational-level amateur sports and through moderate physical activity [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…However, there were no early complications, such as fracture, dislocation, or migration of the cup or stem [9]. In 2017, Czech et al reported that hip joint arthroplasty in people with degenerative joint diseases had a beneficial effect on their level of functioning and physical activity [10]. In addition, Ortmaier et al reported that about 80% of patients returned to sports after short-stem THA, with almost no pain in the affected hip [11].…”
Section: Kijima Et Al Previously Investigated How Many Patients Restmentioning
confidence: 99%
“…rative Status nicht erfasst wurde.Rading und Köster (2011) zeigten mit dem MAYO-Schaft einen Anstieg des UCLA von 3,7 auf 6,3 postoperativ, allerdings bei einem Follow-up von sechs Jahren. In Studien nach sechs beziehungsweise fünf Jahren mit dem NANOS-Schaft lag der UCLA präoperativ bei 2,9 und postoperativ bei sechs beziehungsweise 6.3(Capone et al 2017;Czech et al 2017).Grundsätzlich lässt sich erkennen, dass die körperliche Aktivität nach Implantation des Systems in dem zu erwartenden Bereich liegt und somit ein angemessenes Aktivitätsniveau erzielt wird.…”
unclassified